Les origines marxiennes de l’institutionnalisme monétaire - Raphaël Porcherot (Revue de la Régulation)
The two currents of French monetary institutionalism, monetary analysis and monetary approach, exhibit a filiation relationship with Marx. While they effectively overcome the lack of real monetary thought plaguing Neo-Ricardian and Neo-Classical theory, they have significant theoretical costs. The monetary institution does recover in theory its real-life centrality. But restricting the reflection on value to its qualitative dimension alone, which is especially the case of the monetary approach, tends to leave aside the question of the quantitative determination of exchange ratios and profit rate. We propose to recover the definition of abstract labour as the immanent measure of the value expressed in prices to delimit a field of articulation between monetary institutionalism and Marxism.